2015
DOI: 10.1177/1933719115592713
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenetic Mechanisms of Deep Infiltrating Endometriosis

Abstract: Endometriosis is a benign gynecologic disease, affecting women of reproductive age associated with chronic pelvic pain, dysmenorrhea, dyspareunia and infertility. Ovarian endometrioma (OMA), superficial peritoneal endometriosis (SPE), and deep infiltrating endometriosis (DIE) are, till now, recognized as major phenotypes. The discussion is to know whether they share the same pathogenetic mechanisms. Till today, DIE is recognized as the most severe clinical form of endometriosis and has a complex clinical manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
111
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(127 citation statements)
references
References 69 publications
10
111
0
6
Order By: Relevance
“…High levels of ROS are generated in endometriosis and induce cell damage and proliferation [61], which supports the important role of peritoneal macrophages in the secretion of pro-inflammatory/proangiogenic cytokines [56,62]. Our findings demonstrated that the presence of F4/80-positive macrophages and NO concentrations were higher in endometriotic lesions and statistically reduced in animals treated with açaí.…”
Section: Discussionsupporting
confidence: 81%
“…High levels of ROS are generated in endometriosis and induce cell damage and proliferation [61], which supports the important role of peritoneal macrophages in the secretion of pro-inflammatory/proangiogenic cytokines [56,62]. Our findings demonstrated that the presence of F4/80-positive macrophages and NO concentrations were higher in endometriotic lesions and statistically reduced in animals treated with açaí.…”
Section: Discussionsupporting
confidence: 81%
“…Deep infiltrating endometriosis is characterized by nodules that locally invade pelvic structures, producing symptoms such as painful intercourse (deep dyspareunia) and painful bowel movements (dyschezia). 5 Progestin-based hormonal therapy and gonadotropin-releasing hormone analogues have become the standard treatments; however, many patients have unacceptable systemic adverse effects in association with either or both treatments. 1,6 Moreover, not all women with endometriosis have a response to hormonal therapy, particularly those who have deeply infiltrating disease.…”
mentioning
confidence: 99%
“…Гете-рогенность заболевания отражает различия в уровне экспрессии генов, связанных с гипоксией и ангиоге-незом, предполагая, что такое состояние может играть активную роль в развитии заболевания. Зна-чительные различия, наблюдающиеся между DIE и OMA, подтверждают идею, что DIE и OMA являются двумя разными проявлениями эндометриоза [45]. Различные фенотипы эндометриоза показывают разный уровень экспрессии генов, связанных с ги-поксией и ангиогенезом, поддерживая гипотезу, что такие состояния могут способствовать не только раз-витию эндометриоза, но и его началу [30].…”
Section: ангиогенезunclassified